Highly Reliable and Low-Cost Fabrication of Warm-White LEDs Using Composite Silica Photonic Crystals - Chun-Feng Lai; Yu-Chun Lee; Tzong-Liang Tsai; Chung-Chieh Chang; Mau-Kuen Wu (International Journal of Photoenergy)
We demonstrated a technique requiring little phosphor that used white light-emitting diodes (WLEDs) containing composite silica colloidal photonic crystals (c-SCPhCs) for developing the warm-WLEDs (w-WLEDs). WLEDs containing c-SCPhCs enhanced luminous efficacy 5.6% more than commercial w-WLEDs did. We used a UV adhesive curing method to improve the adhesion properties of the c-SCPhCs. A reliability analysis (RA) test was performed on the WLEDs containing c-SCPhCs, applying a high temperature and high relative humidity (85°C/85 RH) during WLEDs operation at 120 mA. During a RA test of 2500 h, no visible degradation in optical performance was observed. We implemented a novel, inexpensive technique for producing high luminous flux w-WLEDs that can be used in residential light.